Evaluation of the Tissue Reaction to Fast Endodontic Cement (CER) and Angelus MTA - Gomes Filho, João Eduardo [UNESP]; Rodrigues, Guilherme [UNESP]; Watanabe, Simone [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Lodi, Carolina Simonett [UNESP]; Gomes, Alessandra Cristina [UNESP]; Faria, Max Doulgas [UNESP]; dos Santos, Alailson Domingos [UNESP]; Silos Moraes, Joao Carlos [UNESP] (Elsevier B.V., 2009)
Introduction: A new cement (CER; Cimento Endodontico Rapido or fast endodontic cement) has been developed to improve handling properties. It is a formulation that has Portland cement in gel. However, there had not yet been any study evaluating its biologic properties. The purpose of this study was to evaluate the rat subcutaneous tissue response to CER and Angelus MTA. Methods: The materials were placed in polyethylene tubes and implanted into dorsal connective tissue of Wistar rats for 7, 30, and 60 days. The specimens were prepared to be stained with hematoxylin-eosin or von Kossa or not stained for polarized light. The presence of inflammation, predominant cell type, calcification, and thickness of fibrous connective tissue were recorded. Scores were defined as follows: 0, none or few inflammatory cells, no reaction; 1, <25 cells, mild reaction; 2, 25-125 cells, moderate reaction; 3, >125 cells, severe reaction. Fibrous capsule was categorized as thin when thickness was <150 mu m and thick at >150 mu m. Necrosis and formation of calcification were both recorded. Results: Both materials Angelus MTA and CER caused moderate reactions at 7 days, which decreased with time. The response was similar to the control at 30 and 60 days with Angelus MTA and CER, characterized by organized connective tissue and presence of some chronic inflammatory cells. Mineralization and granulations birefringent to polarized light were observed with both materials. Conclusions: It was possible to conclude that CER was biocompatible and stimulated mineralization. (J Endod 2009,35:1377-1380)
Keywords: Biocompatibility; connective tissue; MTA